Analyzing differences in customer satisfaction on the video streaming platform Netflix - Shun-Hsing Chen; Yang-Ju Chen; Wing-Ching Leung (goodwood publishing, 2023)
Purpose: With the rise of online video streaming platforms and the preventive measures taken during the COVID-19 pandemic, staying at home has become the preferred choice for people. As a result, online video streaming platforms, one of the components of the home economy, have experienced rapid growth. Netflix is a subscription-based service that offers movies and TV shows, delivering media content to subscribers through internet streaming. Research methodology: This study utilizes the Importance-Satisfaction Model (I-S Model) as a research tool to explore customer satisfaction levels. Through literature review and expert confirmation, 16 key quality factors were identified for conducting importance and satisfaction surveys among Netflix customers. Additionally, demographic variables such as gender, marital status, education level, occupation, and age were analyzed for differences in the Importance-Satisfaction Model. Results: The study reveals that out of the overall Importance-Satisfaction Model, 2 factors fall in the